Interleukin-33: Metabolic checkpoints, metabolic processes, and epigenetic regulation in immune cells - Lin, Jian; Liu, Jiyun; Ma, Rui; Hao, Jie; Liang, Yan; Zhao, Junjie; Zhang, Ailing; Meng, Haiyang; Lu, Jingli (Frontiers in Immunology, 2022)
Interleukin-33 (IL-33) is a pleiotropic cytokine linked to various immune cells in the innate and adaptive immune systems. Recent studies of the effects of IL-33 on immune cells are beginning to reveal its regulatory mechanisms at the levels of cellular metabolism and epigenetic modifications. In response to IL-33 stimulation, these programs are intertwined with transcriptional programs, ultimately determining the fate of immune cells. Understanding these specific molecular events will help to explain the complex role of IL-33 in immune cells, thereby guiding the development of new strategies for immune intervention. Here, we highlight recent findings that reveal how IL-33, acting as an intracellular nuclear factor or an extracellular cytokine, alters metabolic checkpoints and cellular metabolism, which coordinately contribute to cell growth and function. We also discuss recent studies supporting the role of IL-33 in epigenetic alterations and speculate about the mechanisms underlying this relationship.